Towards Distributed BPEL Orchestrations - Baresi, Luciano; Maurino, Andrea; Modafferi, Stefano (Electronic Communications of the EASST, 2007)
Web services are imposing as the technology to integrate highly heterogeneous systems. BPEL, the standard technology to compose services, assumes a single âorchestratorâ that controls the execution flow and coordinates the interactions with selected services. This centralized approach simplifies the coordination among components, but it is also a too heavy constraint. To this end, the paper introduces the idea of distributed orchestrations and presents a proposal to couple BPEL and distributed execution in mobile settings. The approach âexemplified on a simple case studyâ transforms a centralized BPEL process into a set of coordinated processes. An explicit meta-model and graph transformation supply the formal grounding to obtain a set of related processes, and to add the communication infrastructure among the newly created processes. The paper also presents a communication infrastructure based on tuple spaces to make the different orchestrators interact in mobile contexts. Keywords: WS-BPEL, Graph